RESERVOIR CHARACTERIZATION AND STORAGE CAPACITY OF CO2 ESTIMATION AT RK FIELD, BEKASAP FORMATION, CENTRAL SUMATERA BASIN - Fatimah Saffanah, Kania
Many countries commited to reducing CO2 emission which is a current environmental issue because it is really rises every year. Carbon Capture, Utilization and Storage (CCUS) is essential tool to unlock the full potential decarbonization where the CO2 is captured from atmosphere directly or from refinery & petrochemical plant and geothermal power plant. One of CO2 geological storage is depleted oil and gas field. RK Field is a gas field located in Central Sumatera Basin which has a recovery factor of gas about 48,13% and 14 inactive wells from 18 total wells. Characterization of reservoir and estimation of CO2 storage capacity are needed to identify CCUS potential in interval of study at RK field. This study conducted within SB 1 – SB 5 interval of Early Miocene age in Bekasap Formation. This study aims to understand RK Field’s geological configuration especially in study’s interval, do facies analysis and determine depositional environment of study’s interval, identify and correlate sequence of stratigraphy of study’s interval, determine petrophysics property value in every parasequence of study’s interval, and estimate storage capacity of CO2 of RK Field. Data used in this study came consists of wireline logs from 16 wells, core descriptions, pressure and temperature of reservoir reports, and three-dimension seismic that covers all wells. Seismic of the study area shows several faults of inversion faults with northwest– southeast relative directions. Facies and depositional environment yielded four lithofacies. Lithofacies analysis is then matched with log pattern in electrofacies analysis resulting SB 1 – SB 5 interval shows two facies association which are heterolithic mouthbars and tidally influence channel deposited in delta-front and lower delta plain environment respectively. Sequence stratigraphy analysis shows study’s interval is dominated by progradation and retrogradation parasequence set, transgressive system tract, and highstand system tract. Petrophysics analysis shows the average property value of shale volumes, effective porosity, and water saturation of reservoir is 0.33, 0.12, and 0.33. Reservoir cut-off property values of shale volume at 0.48, effective porosity at 0.1, and water saturation at 0.52. Storage capacity of CO2 in reservoir estimation results is 7.24 MMT CO2 in vapor phase.